Acoustic identification and taxonomic remarks of Hipposiderids and Rhinolophids (Chiroptera: Hipposideridae, Rhinolophidae) in Tam Dao national park, Northeastern Nietnam - Thong, Vu Dinh (Academia Journal of Biology, 2015)
Hipposiderids and Rhinolophids are referred to all taxa of the two families Hipposideridae and Rhinolophidae, respectively. Their echolocation signals are diagnostic by a dominant “constant frequency” (CF) segment. Each echolocation signal of leaf-nosed bat species consists of two segments (“constant-frequency” and “terminal frequency-modulated”) while that of horseshoe bat species comprises three segments (“initial frequency-modulated”, “constant-frequency” and “terminal frequency-modulated”). Between 2008 and 2014, a series of field surveys was conducted in Tam Dao National Park (TDNP) with particular emphases on taxonomy and echolocation of CF bat species. Results from the surveys indicated that TDNP is a home to three species of Hipposideridae (Hipposideros armiger, H. larvatus and H. pomona) and five species of Rhinolophidae (Rhinolophus affinis, R. luctus, R. macrotis, R. pearsonii and R. pusillus). During the present study, R. luctus was only detected in the field based on a poor echolocation call while all seven remaining species were captured. The CF of the second harmonic and morphological features of each species are clearly distinguished from the respective ones of the remaining species. This paper provides the external and acoustic diagnoses of each species for identification in the field to strengthen survey achievements, monitoring and conservation of CF bats in the park in coming time.